Impaired differentiation of highly proliferative ICOS+-tregs is involved in the transition from low to high disease activity in Systemic Lupus Erythematosus (SLE) patients - Kälble, Florian; Wu, Lisa; Lorenz, Hanns-Martin; Zeier, Martin; Schaier, Matthias; Steinborn-Kröhl, Andrea (International journal of molecular sciences, 2021)
Dysregulations in the differentiation of CD4+-regulatory-T-cells (Tregs) and CD4+-responder-T-cells (Tresps) are involved in the development of active systemic lupus erythematosus (SLE). Three differentiation pathways of highly proliferative inducible costimulatory molecule (ICOS)+- and less proliferative ICOS−-CD45RA+CD31+-recent-thymic-emigrant (RTE)-Tregs/Tresps via CD45RA−CD31+-memory-Tregs/Tresps (CD31+-memory-Tregs/Tresps), their direct proliferation via CD45RA+CD31−-mature naïve (MN)-Tregs/Tresps, and the production and differentiation of resting MN-Tregs/Tresp into CD45RA−CD31−-memory-Tregs/Tresps (CD31−-memory-Tregs/Tresps) were examined in 115 healthy controls, 96 SLE remission patients, and 20 active disease patients using six color flow cytometric analysis. In healthy controls an appropriate sequence of these pathways ensured regular age-dependent differentiation. In SLE patients, an age-independently exaggerated differentiation was observed for all Treg/Tresp subsets, where the increased conversion of resting MN-Tregs/Tresps particularly guaranteed the significantly increased ratios of ICOS+-Tregs/ICOS+-Tresps and ICOS−-Tregs/ICOS−-Tresps during remission. Changes in the differentiation of resting ICOS+-MN-Tresps and ICOS−-MN-Tregs from conversion to proliferation caused a significant shift in the ratio of ICOS+-Tregs/ICOS+-Tresps in favor of ICOS+-Tresps and a further increase in the ratio of ICOS−-Tregs/ICOS−-Tresps with active disease. The differentiation of ICOS+-RTE-Tregs/Tresps seems to be crucial for keeping patients in remission, where their limited production of proliferating resting MN-Tregs may be responsible for the occurrence of active disease flares.
Im Titel ist das Zeichen + hochgestellt
Gesehen am 18.10.2021